Association between appendicular lean mass and chronic obstructive pulmonary disease: epidemiological cross-sectional study and bidirectional Mendelian randomization analysis - Fu, Chengjie; Yang, Hongchang (Frontiers in Nutrition, 2023)
Background: The association of BMI with COPD, and sarcopenia in COPD have been both confirmed by several studies, but research on the relationship and causality of body lean mass and the risk of chronic obstructive pulmonary disease (COPD) remains to be discovered. The purpose of this study was to explore the association between lean mass and COPD risk as well as to further examine the causal relationship in the findings. Methods: 3459 participants from NHANES 2012-2018 were included in the epidemiological cross-sectional study to assess the association between relative lean mass and COPD by restricted spline analysis (RCS) and weighted multiple logistic regression. Furthermore, to verify the causality between lean mass and COPD, a two-sample Mendelian randomization (MR) with inverse variance weighting (IVW) method was used to analyze GWAS data from European ancestry. Genetic data from the UK Biobank for appendicular lean mass (450,243 cases) and lung function (FEV1/FVC) (400,102 cases) together with the FinnGen platform for COPD (6,915 cases and 186,723 controls) were used for MR. Results: Weighted multiple logistic regression showed a significant correlation between relative appendicular lean mass and COPD after adjusting for confounders (OR = 0.985, 95% CI: 0.975-0.995). Compared to the lower mass (432.7-602.5 g/kg), the high mass (708.0-838.5 g/kg) of appendicular lean apparently decreases the risk of COPD (OR = 0.214, 95% CI: 0.060-0.767). Besides, in the analysis of MR, there was a forward causality between appendicular lean mass and COPD (IVW: OR = 0.803; 95%CI: 0.680-0.949; P = 0.01), with a weak trend of causality to lung function. Conclusion: Our study not only found an inverse association between appendicular lean mass and COPD but also supported a unidirectional causality. This provided possible evidence for further identification of people at risk for COPD and prevention of COPD based on limb muscle exercise and nutritional supplementation to maintain skeletal muscle mass.